Використання арт-терапії у соціальній роботі з особами з інвалідністю - Буханиста, Наталія (БДПУ, 2023)
У кваліфікаційній роботі визначеносутність арт-терапії у соціальній роботі; охарактеризовано методи арт-терапії та особливості використання їх у соціальній роботі з особами з інвалідністю; проаналізовано досвід використання арт-терапії в роботі з людьми з інвалідністю; розроблено рекомендації щодо підвищення ефективності використання арт-терапії у соціальній роботі з особами з інвалідністю.
Use of art therapy in social work with persons with disabilities
In the qualification work, the determinability of art therapy in social work; methods of art therapy and features of their use in social work with persons with disabilities are characterized; the experience of using art therapy in working with people with disabilities is analyzed; recommendations for increasing the effectiveness of art therapy in social work with persons with disabilities.
Keywords: особи з інвалідністю; арт-терапія; методи арт-терапії; соціальна робота з особами з інвалідністю; persons with disabilities; art therapy; methods of art therapy; social work with persons with disabilities